‘Taking Time’ – Extended mental health consultations in a deprived urban general practice: A retrospective descriptive study - Siobhan Hinchy; Eimear Pilkington; Helen Tobin; Nandakumar Ravichandran; Walter Cullen; Brian O’Donoghue; Bobby Smyth; Anna Beug (PLoS ONE, 2026)
Background Mental health presentations are common in general practice, particularly in socially deprived areas, yet standard consultation times often limit GPs’ ability to comprehensively assess and manage patients presenting with diverse emotional concerns. Such work is also difficult to capture in research, which often relies on coded diagnoses or prescribing data. This study aimed to describe the nature, management, and outcomes of extended mental health consultations in a deprived urban Irish practice. Methods A retrospective descriptive secondary analysis was conducted on clinical charts for 195 patients who attended 30-minute extended mental health consultations between March 2021 and March 2023. Quantitative data on demographics, presenting complaints, prescriptions, and referrals were analysed descriptively, while clinical notes were systematically categorised to explore the spectrum of emotional concerns. Results The median patient age was 29.0 years; 63.1% were female, and 69.8% lived in areas below the national average for social deprivation. Anxiety (47.7%) and low mood (42.1%) were the most common presenting complaints. Psychotropic prescriptions were initiated or modified for 37.9% of patients, with SSRIs the most prescribed. Of all patients, 26.7% were referred to psychiatric services and 57.4% were signposted to community mental health supports. Conclusion The study demonstrated GPs in this deprived urban practice encountered wide range of mental health concerns across all ages and managed substantial proportion entirely within the community. These findings highlight the potential for delivering mental health care in general practice when time and resources are sufficient and underscore the need for better access to comprehensive primary care mental health supports.